Sarvodaya and development : multi-disciplinary perspective from Musahari - Sachchidananda, 1926- (A.N.S. Institute of Social Studies : sole-distributor, Associated Book Agency, 1976)
Study of the rural self-rule (gramswaraj) movement in Musahari Block, Muzaffarpur District, Bihar, 1970.